Microencapsulation of Plant Phenolic Extracts Using Complex Coacervation Incorporated in Ultrafiltered Cheese Against AlCl3-Induced Neuroinflammation in Rats - Soliman, Tarek N.; Mohammed, Dina Mostafa; El-Messery, Tamer M.; Elaaser, Mostafa; Zaky, Ahmed A.; Eun, Jong-Bang; Shim, Jae-Han; El-Said, Marwa M. (Frontiers in Nutrition, 2022)
Plant-derived phenolic compounds have numerous biological effects, including antioxidant, anti-inflammatory, and neuroprotective effects. However, their application is limited because they are degraded under environmental conditions. The aim of this study was to microencapsulate plant phenolic extracts using a complex coacervation method to mitigate this problem. Red beet (RB), broccoli (BR), and spinach leaf (SL) phenolic extracts were encapsulated by complex coacervation. The characteristics of complex coacervates [zeta potential, encapsulation efficiency (EE), FTIR, and morphology] were evaluated. The RB, BR, and SL complex coacervates were incorporated into an ultrafiltered (UF) cheese system. The chemical properties, pH, texture profile, microstructure, and sensory properties of UF cheese with coacervates were determined. In total, 54 male Sprague–Dawley rats were used, among which 48 rats were administered an oral dose of AlCl3 (100 mg/kg body weight/d). Nutritional and biochemical parameters, including malondialdehyde, superoxide dismutase, catalase, reduced glutathione, nitric oxide, acetylcholinesterase, butyrylcholinesterase, dopamine, 5-hydroxytryptamine, brain-derived neurotrophic factor, and glial fibrillary acidic protein, were assessed. The RB, BR, and SL phenolic extracts were successfully encapsulated. The RB, BR, and SL complex coacervates had no impact on the chemical composition of UF cheese. The structure of the RB, BR, and SL complex coacervates in UF cheese was the most stable. The hardness of UF cheese was progressively enhanced by using the RB, BR, and SL complex coacervates. The sensory characteristics of the UF cheese samples achieved good scores and were viable for inclusion in food systems. Additionally, these microcapsules improved metabolic strategies and neurobehavioral systems and enhanced the protein biosynthesis of rat brains. Both forms failed to induce any severe side effects in any experimental group. It can be concluded that the microencapsulation of plant phenolic extracts using a complex coacervation technique protected rats against AlCl3-induced neuroinflammation. This finding might be of interest to food producers and researchers aiming to deliver natural bioactive compounds in the most acceptable manner (i.e., food).